Desenvolvimento de fases estacionárias baseadas em poli(óxido de etileno-co-dimetilsiloxano) imobilizado termicamente sobre sílica para cromatografia líquida de interação hidrofílica - Carvalho, Giselle de Oliveira (2017)
Stationary phases for separation of polar compounds have been the focus of development in chromatography, since these substances present difficulty of retention in the reversed phase and irreversible retention in the normal phase chromatography. This work presents the preparation of a new stationary phase for the separation of hydrophilic substances. For this, the general objective of this work was to prepare a stationary phase based on the thermal immobilization of poly(ethylene oxide-co-dimethylsiloxane) (PEO) onto silica particles (5 μm). The polymer studied and the stationary phases prepared were characterized physicochemically and chromatographically. The physicochemical characterization results were obtained by scanning electron microscopy, infrared absorption spectroscopy, thermogravimetric analysis and elemental analysis. These results indicated that the polymer was immobilized on silica surface. It was verified that the Si(PEO) phase can act in the reverse phase mode and has hydrophilic interaction suitable for polar compounds, since it was able to separate efficiently polar compounds from Tanaka protocol. With the application of a fractional factorial design, it was possible to verify which experimental variables can influence significantly the incorporation of the polymer in the support of silica (solvent of the reaction medium, time and temperature of immobilization, polymeric load). Through a central composite design, it was possible to determine the optimal preparation conditions of stationary phase taking in account the loading of polymeric PEO and the immobilization temperature. From the results, it was considered that the phase prepared under optimum conditions was the Si(PEO) phase prepared in chloroform, with a loading of PEO as 50% w/w, temperature and immobilization time of 100 °C and 16 h, respectively. The Si(PEO) phase presents potential in the separation of polar substances, such as pharmaceuticals and agrochemical residues, requiring mobile phase with high aqueous solvent composition, making it an interesting material for the Per-Aqueous Liquid Chromatography, promoting a significant reduction of organic residues from chromatographic process, and consequently contributing to the advancement of green liquid chromatography. In addition, the Si(PEO) phase has a great attractiveness of practicality, low cost and ease of preparation, requiring simple and low-cost materials and instrumentation.